The story of moose an agile reengineering environment. - Nierstrasz, Oscar (Software engineering notes.)
MOOSE is a language-independent environment for reverse- and re-engineering complex software systems. MOOSE provides a set of services including a common meta-model, metrics evaluation and visualization, a model repository, and generic GUI support for querying, browsing and grouping. The development effort invested in MOOSE has paid off in precisely those research activities that benefit from applying a combination of complementary techniques. We describe how MOOSE has evolved over the years, we draw a number of lessons learned from our experience, and we outline the present and future of MOOSE.